Climate station data from the Laforge Reservoir region, Quebec, Canada : Données des stations climatiques de la région du Réservoir Laforge, Québec, Canada - Centre D'études Nordiques (Nordicana D, 2020)
Data are from the Laforge Reservoir region, Quebec, Canada. It contains data from air and ground temperatures, air humidity, solar radiation, wind speed and direction and the average snow height. The available datasets cover the period from 1995-2013. For each site, the number of measured variables differs. For ground temperature, the depth ranges are as follows: Réservoir Laforge 1 (LAFORG1) : 20 cm Trans Taiga (LGTAIGA) : 0-25 cm Data are available as: (1) recorded data; (2) daily averages; (3) monthly averages; and (4) yearly averages. : Les données proviennent de la région du réservoir Laforge, Québec, Canada. On y retrouve des données de température de l'air et du sol, de radiation solaire, de vitesse et de direction des vents. La période couverte par les données est 1995-2013. Pour chaque site, le nombre de variables mesurées varie. Pour les données de température de sol, les intervalles de profondeur sont: Réservoir Laforge 1 (LAFORG1) : 20 cm. Trans Taiga (LGTAIGA) : 0-25 cm. Les données sont disponibles en quatre formats: (1) données enregistrées; (2) la moyennne journalière; (3) la moyenne mensuelle et (4) la moyenne annuelle.